2016
DOI: 10.1590/0102-311x00174014
|View full text |Cite
|
Sign up to set email alerts
|

Excesso de peso/obesidade no ciclo da vida e composição corporal na idade adulta: coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1982

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(30 reference statements)
0
3
0
7
Order By: Relevance
“…A previous study from this same cohort showed that a continuous exposure to overweight was associated with higher fat mass in adulthood showing a cumulative effect, whereas those who were overweight only at childhood or adolescence presented similar body composition to those who were never overweight [26]. In this study, most of the effect of overweight trajectory on the cardio metabolic risk factors was captured by fat mass.…”
Section: Discussionmentioning
confidence: 53%
“…A previous study from this same cohort showed that a continuous exposure to overweight was associated with higher fat mass in adulthood showing a cumulative effect, whereas those who were overweight only at childhood or adolescence presented similar body composition to those who were never overweight [26]. In this study, most of the effect of overweight trajectory on the cardio metabolic risk factors was captured by fat mass.…”
Section: Discussionmentioning
confidence: 53%
“…Considerando o exposto, a fase da adolescência pode ser definidora dos hábitos alimentares ao longo do ciclo vital e os estudos vêm mostrando sistematicamente que esse consumo está inadequado [10][11][12] . Nesse sentido, considera-se o ambiente escolar como importante meio para a educação alimentar e nutricional 13,14 .…”
Section: Introductionunclassified
“…Tal fato tem sido atribuído às modificações do estilo de vida, ao aumento das taxas de sobrepeso e obesidade e ao envelhecimento populacional (MATOS EC, et al, 2018). Os achados do estudo evidenciaram que o IMC, apresentou média de 28,4 Kg/m² e conforme a Organização Mundial de Saúde (OMS), valores de IMC ≥ a 25,0 e < 30,0 indicam adulto com sobrepeso (CALLO G, et al, 2016).…”
Section: Discussionunclassified